Gentry life in Georgian Ireland : the letters of Edmund Spencer (1711-1790) - Spencer, Edmund (Legenda, Modern Humanites Research Association, 2017)
Parental profligacy and the dishonesty of his guardian meant that when Edmund Spencer came of age in 1732 he inherited only a fragment of the estates that his great-great-grandfather, the Elizabethan poet Edmund Spenser, had amassed in Ireland. To keep himself and his family in a manner appropriate to their status Spencer had to find an income. His plan to publish the collected works of his ancestor foundered on the unrest caused by the 1745 Jacobite rebellion; posts in the army and the revenue proved just as elusive. In this collection of 120 letters, written to relatives in Wales, we follow his sometimes desperate hunt for preferment in Dublin and elsewhere, making full use of an extended network of patronage which includes, rather surprisingly, a number of Jacobite sympathisers. Along the way he paints a vivid picture of everyday life in eighteenth century rural Ireland, deploring bad harvests, making fun of extravagant spending at elections, dispensing alarming medical advice as well as passing on news about deaths and marriages, and gossip about elopements. This annotated edition of Spencer's letters will be of interest to both scholars and general readers eager to learn more about life in Georgian Ireland.